PENGARUH FINANCIAL INCLUSION TERHADAP PEREKONOMIAN INDONESIA - Trevie Della Bonivia; Hasdi Aimon; Alpon Satrianto (Universitas Negeri Padang, 2019)
The Study aims to analyzed the effect of number of branches bank inclusion, ATM machine inclusion, number of deposit accounts inclusion on Indonesian economy. Data used from 2012-2017 that invlove 6 main islands in Indonesia by The Central Bureau of Statistic and CEIC data. The data analysis used regression panel model to estimate the effect of Indonesian economy. The results show that number of branches bank inclusion, ATM machine inclusion an number of deposit accounts inclusion have positive and significant impact on Indonesian economy.